2018
DOI: 10.1177/2045894018762270
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of the reliability of Doppler echocardiographic estimations for mean pulmonary artery pressure in patients with pulmonary hypertension: a study from a tertiary centre comparing four formulae

Abstract: Different Doppler echocardiography (DE) models have been proposed for estimation of mean pulmonary arterial pressures (PAMP) from tricuspid regurgitation (TR) jet velocity. We aimed to compare four TR-derived DE models in predicting the PAMP measured by right heart catheterization (RHC) in different groups of precapillary pulmonary hypertension (PH). A total of 287 patients with hemodynamically pre-capillary PH were enrolled (mean age = 51 ± 17.4 years, 59.9% female). All patients underwent DE before RHC (< 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…RHC measurement, regardless of the underlying pathology(8). Thus, in concordance with the latest guidelines from the European Society of Cardiology and European…”
supporting
confidence: 82%
See 1 more Smart Citation
“…RHC measurement, regardless of the underlying pathology(8). Thus, in concordance with the latest guidelines from the European Society of Cardiology and European…”
supporting
confidence: 82%
“… 7 On the other hand, there is a poor agreement between echocardiographic mean PAP estimates (four tricuspid regurgitation jet-derived) and RHC measurement, regardless of the underlying pathology. 8 Thus, in concordance with the latest guidelines from the European Society of Cardiology and European Respiratory Society, TTE should only be used as the first-line screening modality. 5 With improvements in the echocardiographic evaluation of the right ventricular function, TTE has become a valuable tool in the follow-up of patients.…”
mentioning
confidence: 99%
“…Thus, our data suggest that when PA pressure can be measured by echocardiography, this is an effective screening tool for detecting patients at risk for mild PH who may benefit from further evaluation, close follow‐up, and risk reduction interventions 17, 20. Nonetheless, a recent study in patients with PH (mPAP >25 mm Hg) demonstrated modest correlation and poor agreement between echocardiography‐derived and RHC‐measured PASP and mPAP 28. Fisher et al29 showed that approximately half of the cases of PASP overestimation are related solely to right atrial pressure overestimation by echocardiography.…”
Section: Discussionmentioning
confidence: 76%
“…Right ventricular systolic pressure and pulmonary artery (PA) systolic pressure are equal in the absence of right ventricular outflow obstruction and pulmonary stenosis [26]. The mean PA pressure can be derived from echocardiographic measurement of the systolic pulmonary artery pressure [27] and the diastolic pulmonary artery pressure [7] or from PA acceleration time [28], however there is substantial potential for error. Echocardiography can also be used to calculate pulmonary vascular resistance, using the TR-jet and RVOT time-velocity integral (TVI) [29], but lacks accuracy, particularly for serial assessment [30].…”
Section: Important Clinical Applications Pulmonary Hypertensionmentioning
confidence: 99%